Model Pembelajaran Untuk Meningkatkan Keterampilan Proses Ipa-Asesmen Dan Pembelajaran Tematik Calon Guru Sekolah Dasar - Siahaan, Parsaoran; Liliasari, Liliasari (BERKALA FISIKA, 2010)
This research is part of a series of research and development to improve the mastery learning model of prospective elementary school teachers in science and pembelajarannya.Model learning concepts developed in this research is the learning model that integrates two different courses are semester courses the concept of science and science education. Scenario learning is done in four phases, namely: (1). Modeling phase, (2) phase of discussion, (3). Enrichment phase, and (4) peer learning phase. The study was conducted on students of teacher candidates in two PGSD who take shelter in the Indonesian Education University of PGSD X sekota with the University and PGSD Y berdomosili in other cities within the same province.Subjects consisted of 25 students in PGSD X prospective teachers and 26 student teacher candidates at PGSD Y. The material consists of three pairs of research topics Magnet-Process Skills Science, Electrical-assessment in learning science and food-Thematic Learning. The research instrument used in the form of multiple choice tests and Description. Analysis of data using <g> dinormalisir gain from Hake. Research shows <g> PGSD X student teacher candidates related to science process skills and assessment including the classification was 0.57 ± 0.10 and high classification in thematic learning that is equal to 0.70 ± 0.14, whereas <g> student-teacher candidates PGSD Y including the classification is to Skills Assessment Process science and is equal to 0.68 ± 0.07, and medium for learning thematic classification that is equal to 0.53 ± 0.20. From <g> acquisition can be concluded that student teacher candidates PGSD PGSD Y better than X in Science Process Skills - Assessment, but lower in the Thematic learning. Key words: learning model, prospective teachers, science process skills, assessment, thematic.